"Eficiencia de la valoración de la prueba en le trámite del proceso penal y la vulneración de los derechos constitucionales del imputado" - Vélez Segovia, Yahaira Elizabeth (2013)
This research aims to establish parameters to guide the application of sound judgment in the valuation activity of the judge as to the evidence , focusing on criminal matters since it is where there is more controversy due to public concern that have caused some criminal cases that have gone unpunished . To perform a valid study to obtain reliable results the design of the thesis is divided into four chapters. In the first chapter the research problem described, establishing the location of the problem under study, justification, determining the core problem and complementary, consistent with the objectives and hypotheses raised to correctly identify and direct the research work. In the Second Chapter, conceptual, legal and administrative context to support thematic detailed theoretical framework , referring to the Criminal Law, Criminal Procedure , evidence and assessment, sound judgment, and to establish the context in which they perform the research and the rules governing it . In the Third and Fourth Chapter, the methodology used in the research work is defined, in addition to analyze, interpret and tabulate all the information gathered through field surveys of judges of the Courts of Criminal Guarantees, prosecutors, lawyers in private practice and citizenship of the city of Quevedo. A proposed amendment to Article 86 of the Code of Criminal Procedure with the respective reasoning is presented in Chapter Six. It also presents some annexes detailing the research process done